LiBaWF9 KRISTALLARNING XUSUSIY LYUMINESSENSIYASI - Nuritdinov, I.; Atashov, B.T.; Yuldashov, D.P.; Oralbayev, K.G. (SCIENCE and SOCIETY, 2023)
The intrinsic recombination luminescence of LiBaWF9 crystals was studied on the basis of the temperature dependence of X-ray luminescence.